The missing story behind Genome Wide Association Studies: single nucleotide polymorphisms in gene deserts have a story to tell - Schierding, William S.; Cutfield, Wayne S.; O'Sullivan, Justin M. (Frontiers in Genetics, 2014)
Genome wide association studies are central to the evolution of personalized medicine. However, the propensity for SNPs to fall outside of genes means that understanding how these polymorphisms alter cellular function requires an expanded view of human genetics. Integrating the study of genome structure (chromosome conformation capture) into its function opens up new avenues of exploration. Changes in the epigenome associated with SNPs in gene deserts will allow us to define complex diseases in a much clearer manner, and usher in a new era of disease pathway exploration.